BIOPHYSICS OF HEAT EXCHANGE IN THE HUMAN BODY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The biophysics of heat exchange governs how the human body maintains a stable core temperature by balancing internal metabolic heat production with physical and environmental transfer mechanisms. Heat gain arises as a byproduct of cellular metabolism and/or exposure to external temperatures greater than the body surface. Heat loss occurs via conduction, convection, radiation and evaporation, the rates of which are governed by the physical properties of the skin (surface area, skin temperature and wettedness) and the environment (ambient and radiant temperatures, air movement, barometric pressure, ambient vapor pressure, clothing insulation) (Gagge and Nishi, 1977). The purpose of this review is to present a current understanding of the biophysical factors that contribute to individual variability in the thermoregulatory responses to heat.
Keywords: Thermoregulation, Metabolic Heat Production, Conduction, Convection, Radiation, Evaporation, Thermal Homeostasis, Human Physiology, Oxygen Consumption (VO₂), Heat Balance Equation, Thermal Energy